Towards a viable system for monitoring agrobiodiversity on-farm: A proposed new approach for Red Listing of cultivated plant species - Padulosi, S.; Dulloo, Mohammad Ehsan (Bioversity International, 2012)
The development of a system for the monitoring of agrobiodiversity in situ or on-farm is of paramount importance for every country and urgently needed. Its importance arises from the fact that by and large the greatest amount (inter- and intra-specific levels) of agrobiodiversity (plants and animals) is maintained in situ or on-farm and no monitoring system yet exists. Its urgency is justified on the grounds of the extensive genetic erosion taking place in farmers fields, and the need to prevent this before it is too late. Concerns for the loss of traditional crops seem to be increasing today among decision-makers, particularly in the context of climate change and the reduced adaptation and resilience of production systems with which this phenomenon is associated. In fact, from a livelihood perspective, loss of agrobiodiversity has a far greater impact, particularly on the poor, in terms of reduced options related to food security, income generation, environmental health and loss of many other intangible benefits. Monitoring of cultivated agrobiodiversity has, not surprisingly, received extremely poor attention by researchers so far. Reasons for that may include the sheer number of varieties of crop species on-farm, the diffuse presence of diversity, varying from large areas to small patches of land and home gardens, the dynamic nature of cultivation that deploys various crops and varieties in different ways, the absence of farmer based mechanisms to which to anchor a possible monitoring system, and important policy aspects, such as those related to access and use of information generated during the monitoring. After reviewing the importance of on-farm conservation, we present an initial framework for the monitoring of cultivated plant biodiversity on-farm.